PENERAPAN MODEL QUANTUM TEACHING DENGAN MEDIA GRAFIS DALAM PENINGKATAN PEMBELAJARAN PECAHAN PADA SISWA KELAS V SD N MUJUR 01 TAHUN AJARAN 2015/2016 - Rahmawati, Desi (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Quantum Teaching Model Using Graphic Media in Improving Teaching about Fraction for the Fifth Grade Students of SD Negeri 1 Mujur in the Academic Year of 2015/2016. The objectives of this research is to improve learning about fraction through the application of Quantum Teaching model for the fifth grade students. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Techniques of collecting data were observation, interview, documentation, and test. The results of this research showed that the application of Quantum Teaching using graphic media can improve students? learning outcomes about fraction for the fifth grade students. Keywords: Quantum Teaching, graphic media, fraction